Predicting the past : the paradoxes of American literary history - Boyden, Michael (Leuven University Press, 2009)
Drawing from the social theories of Niklas Luhmann and Mary Douglas, Predicting the Past advocates a reflexive understanding of the paradoxical institutional dynamic of American literary history as a professional discipline and field of study. Contrary to most disciplinary accounts, Michael Boyden resists the utopian impulse to offer supposedly definitive solutions for the legitimation crises besetting American literature studies by ""going beyond"" its inherited racist, classist, and sexist underpinnings. Approaching the existence of the American literary tradition as a typically modern probl.